Market Regulation, Cycles and Growth in a Monetary Union - Abbritti, Mirko (IMF Working Papers; Working Paper ;, 2019)
We build a two-country currency union DSGE model with endogenous growth to assess the role of cross-country differences in product and labor market regulations for long-term growth and for the adjustment to shocks. We show that with endogenous growth, there is no reason to expect real income convergence. Large shocks, through endogenous TFP movements, can lead to permanent changes of output and real exchange rates. Differences are exacerbated when member countries have different product and labor market regulations. Less regulated economies are likely to have higher trend growth and recover faster from negative shocks. Results are consistent with higher inflation, lower employment and disappointing TFP growth rates experienced in the less reform-friendly euro area members.